Deign of Millimeter-Wave Antennas for 5G - Min, Foo Ze; Al-Fadhali, Najib; Majid, Huda; Jumadi; Shairi, Azwan; M. Gisamalla, Mohammed S.; Ashyp, Adel; Mukred, Jamil; Abo Mosali, Najmaddin (Journal of Advanced Industrial Technology and Application, 2023)
The evolution of 5G is became a common in this decade and characteristic of 5G provide high speed and low latency provoke the demand of development of millimeter wave antenna. This project is to design a compact millimeter-wave antennas for 5G at 28GHz using CST Studio Suite and validation of simulated result using fabrication and measurements. The double side FR-4 with thickness of 1.6 mm and dielectric constant of 4.7, copper with thickness 0.035mm is used and microstrip feed line is used as feeding technique to the antenna. The CST Studio Suite used in simulation and obtain reflection coefficient of -45.11 dB, 1.011 VSMR, gain of 5.472 dBi and directivity of 6.694 dBi at 28 GHz. The measured result obtain 27.776 GHz with -19.18 dB using VNA